Approach of Care among Depression Patients with Coronary Artery Disease: A Literature Review - Mahendra, Agus (Scientia Psychiatrica, 2023)
Patients with coronary artery disease (CAD) frequently experience psychiatric morbidity, such as depression. It's still unknown how pre-existing depression affects mortality in people with coronary artery disease (CAD). The study's overall goal was to discover depression among patients with coronary artery disease. The detection of psychological problems (depression) in individuals with CAD has been proven to improve prognosis and quality of life. Patients who are being treated for depression or anxiety may be more likely to stick to risk factor reduction, recommended medications, and rehabilitation programs. As a result, patients with known CAD and psychiatric illnesses should be assessed.